Reducing nitrogen loss by application of natural clinoptilolite modified with quaternary N-Alkyl agent as controlled-release fertilizer in two species of beans (P. Vulgaris and Vigna Unguiculata). Issue 13 (20th July 2018) - Heydari, Moslem; Mir, Noshin; Moussavi-Nik, Seyed Mohsen
ABSTRACT: In this work, a novel controlled-release fertilizer (CRF) was designed by using new quaternary N-alkyl as an innovative surface modifier for clinoptilolite in order to adsorb the nitrate anion. So far, a few number of commercial cationic surfactants have been introduced for engineered zeolites to adsorb and slow release anions. Therefore, an organic ligand was synthesized for the first time and was applied for modification of clinoptilolite. Investigating the effect of pH and adsorbent dosage showed that the experimental adsorption data were fitted well with the Langmuir and Freundlich isotherm models. Moreover, nitrate leaching tests were performed and the results confirmed that nitrate concentration of the leachate from the soil amended with novel fertilizer was 42% lower than that of the urea fertilizer. The growth parameters including were studied and the results showed that the red beans planted in the soil amended with modified fertilizer had the best results.